Realismus a jazyk: Recept podle Sellarse - Dach, Stefanie (Organon F, 2014)
Wilfrid Sellars’ philosophical system joins issues that have often been regarded as incompatible or at least in mutual tension. Two of these are his holistic approach to language and knowledge on the one hand and his realism on the other hand. In my paper I first outline this tension and then present a number of steps, including the rejection of semantic relations, picturing and the defense of realism, which can help us to accommodate it. I highlight the payoff of these steps for the question to be solved. In the last part of the paper I detect new and more refined tensions revealed by Sellars’ solution. I identify possible dissonances between his Kantian and his naturalist treatment of causality as well as between his two ways of conceiving of language arguing that these new questions furnish a more interesting approach to our initial problem.
Keywords: causality; constructivism; picturing; realism; semantics; Wilfrid Sellars